Retinal hemorrhage and bleeding disorders in children: A review. (February 2021) - Thau, Avrey; Saffren, Brooke; Zakrzewski, Helena; Anderst, James D.; Carpenter, Shannon L.; Levin, Alex
Abstract: Background: Retinal hemorrhages (RH) are a common manifestation of abusive head trauma (AHT) resulting from acceleration-deceleration injury with or without blunt impact. Evaluation of a child with RH requires careful consideration of these differential diagnoses. The extent to which coagulopathy alone can cause RH would be useful to understand as coagulopathy may accompany AHT. Objective: In this systematic review, we sought to identify whether coagulopathies have been reported with RH similar to those of AHT. Methods: We performed a literature search for ocular manifestations of bleeding disorders in children less than 18 years old. We included clotting factor deficiencies, vitamin K deficiency, platelet function abnormalities, thrombocytopenia, disseminated intravascular coagulation (DIC), and trauma induced coagulopathy (TIC). We included only pediatric reports of intraocular bleeding or documented eye examinations that indicated no hemorrhages. We then re-examined cases for ocular and systemic findings that could potentially mimic abuse. Results: Our initial search yielded 816 results. Sixty-one articles met our inclusion criteria. Of these, there were 32 children within the AHT age range (less than 5 years old) who had RH and concomitant coagulopathy. Only 5 cases might potentially be confused for abuse. Of these, no classic characteristics of RH from abuse such as retinoschisis or retinal folds were found. Systemic features were inconsistent with AHT. Conclusions: The presence of coagulopathy alone does not rule out the possibility that the child has been abused. Coagulopathy alone has not been reported as an etiology of RH that are consistent with AHT, especially when other findings are present.